Systematic diagonal and vertical errors in antisaccades and memory-guided saccades - Mathias Abegg; Hyung Lee; Jason J. S. Barton (Bern Open Publishing, 2010)
Studies of memory-guided saccades in monkeys show an upward bias, while studies of antisaccades in humans show a diagonal effect, a deviation of endpoints toward the 45° diagonal. To determine if these two different spatial biases are specific to different types of saccades, we studied prosaccades, antisaccades and memory-guided saccades in humans. The diagonal effect occurred not with prosaccades but with antisaccades and memory-guided saccades with long intervals, consistent with hypotheses that it originates in computations of goal location under conditions of uncertainty. There was a small upward bias for memory-guided saccades but not prosaccades or antisaccades. Thus this bias is not a general effect of target uncertainty but a property specific to memory-guided saccades.